The Zakat Effect: Evaluasi Dampak Pengelolaan Zakat Pada Bidang Pendidikan Menggunakan Servqual Model - Dendy Herdianto; Nurfala Safitri; Muhammad Abdul Rohman; Muhammad Afif Rifqi; Khairun Nisa (Asyafina Akademik Press, 2022)
Currently, the United Nations is actively campaigning for the Sustainable Development Goals. One of the goals of sustainable development is related to education and poverty. The purpose of this paper is to analyze the factors that most significantly affect the satisfaction of mustahiq zakat, namely the students of SMA Terbuka Depok (a school which is the result of the education program of the Zakat Sukses institution in Depok). The method that will be used is quantitative research using Non-Probability Sampling technique with Stratified Sampling approach. Data analysis used the ordinary least square method using the servqual model method. The results showed that the empathy factor significantly affected mustahiq's satisfaction with educational services held by SMA Terbuka Depok